GeoPOBA as green technology in landfill liner / Atiqah Najwa Zainuddin … [et al.] - Zainuddin, Atiqah Najwa; Mukri, Mazidah; Che Hassan, Asmawati; Yusof, Nurul Ain Umaiban; Che Lat, Diana (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
In the palm oil industry, the waste products of the palm oil boiler ash have become one of the major issues because as a by-product, it is less utilized and dumped in landfills. Geopolymer is a new green technology that has been intensively studied in concrete applications, but few studies on geopolymer have been conducted in soil applications. This aims of this study to investigate the effect of geopolymer in landfill soil liner. The main objective of this study is to develop the Modelling and Nomograph in predicting hydraulic conductivity of landfill soil liner. Different percentages of geopolymer (0%, 5%, 10%, 15%, and 20%) were added to laterite soil. Based on data from the compaction test, 15% of geopolymer in laterite soil indicated the best-mixed design with a maximum dry density of 2.23 Mg/m3 and moisture content of 13.58%. According to compaction measurement, a high value of maximum dry density reduces the air voids, thereby reducing hydraulic conductivity. The SEM images proved the development of geopolymer gel stabilized the soil structure from a loose structure to a denser soil structure. The goal of this study is to analyze the geopolymer of boiler-ash applied to laterite soil as an alternative method in geotechnical applications to increase soil strength and potentially decrease the rate of hydraulic conductivity. As a conclusion, this can be concluded that by geopolymer technology as additives will develop new liner design, reduce hydraulic conductivity, and sustain the environment.